การสอนเภสัชวิทยาในหลักสูตรทันตแพทยศาสตร์ของไทย - แสงศิรินาวิน, เชวงเกียรติ (Journal of Basic and Applied Pharmacology, 2015)
The teaching of pharmacology in 5 dental schools in Thailand was studied through the analysis of information provided by the head of departments. The study focused on the length and content of the courses and professional qualification. The result showed that pharmacology is taugth by using lecture principally. Most of the instructors held M.S. and Ph.D. degree. The lecture hours are quite different between dental schools. It range from 54 to 121 hours, with the mean of 89.2 ± 23.9 hours. Some dental schools are not emphasize on the drugs used in dental practice. The result revealed that the contents in pharmacology curriculum of dental schools in Thailand should be revised.